2021
DOI: 10.4102/sajr.v25i1.2168
|View full text |Cite|
|
Sign up to set email alerts
|

Radiology subspecialisation in Africa: A review of the current status

Abstract: Background: Radiology subspecialisation is well-established in much of Europe, North America, and Australasia. It is a natural evolution of the radiology speciality catalysed by multiple factors.Objectives: The aim of this article is to analyse and provide an overview of the current status of radiology subspecialisation in African countries.Methods: We reviewed English-language articles, reports, and other documents on radiology specialisation and subspecialisation in Africa.Results: There are 54 sovereign cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The role of radiology has evolved from merely medical imaging for diagnostic purposes to utilisation of medical imaging approaches to aid in interventional diagnostic and therapeutic uses [15] . In sub-Saharan Africa there is a lack of interventional radiologists due to lack of resources and expertise hence the conventional open approach for even biopsies for histological analysis is still employed [16] , [17] . Once a metastatic disease is identified the oncological puzzle to look for the primary begins [18] .…”
Section: Discussionmentioning
confidence: 99%
“…The role of radiology has evolved from merely medical imaging for diagnostic purposes to utilisation of medical imaging approaches to aid in interventional diagnostic and therapeutic uses [15] . In sub-Saharan Africa there is a lack of interventional radiologists due to lack of resources and expertise hence the conventional open approach for even biopsies for histological analysis is still employed [16] , [17] . Once a metastatic disease is identified the oncological puzzle to look for the primary begins [18] .…”
Section: Discussionmentioning
confidence: 99%
“…The situation in developing countries such as Africa is much worse, with the ratio being under one radiologist per 1,00,000 population. 5,6 With an increase in the population and the number of radiological examinations performed each year, the relative number of qualified radiologists is declining, resulting in backlogs and delays in timely medical imaging even in large organisations like the UK-National Health Service and the US-Department of Veterans Affairs. [7][8][9] Consequent to the increase in the volume of scans, and a decrease in the number of radiologists, are the issues of increasing radiologist burn-out and high interpretation errors.…”
Section: Introductionmentioning
confidence: 99%
“…The radiology subspecialty must comprise a distinct area of knowledge that cannot be incorporated into the general radiology curriculum. In addition, it must have unique applicability backed up by evidence of improved patient care that a subspecialist's skillset can offer, and structured formal training with apparent benefits that do not negatively impact the existing general radiology training or other radiology subspecialties [ 2 ]. Many factors that drive the interest of a radiologist in pursuing further fellowship training have been identified in the literature, some of which are personal, such as the chance of improving career prospects, while others are job-related [ 3 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Africa suffers from a chronic lack of access to radiology training programs, both at the level of the diagnostic radiology (DR) residency and the radiology specialty (RS) fellowship. It has been shown that only 18 of the 54 sovereign African nations (excluding disputed territories) report having well-established DR residency programs, and only eight of those nations report having any subspecialty programs, with information being readily available for only five of them: Egypt, Ethiopia, Kenya, South Africa, and Tanzania [ 2 ]. In Africa, radiology postgraduate residency and subspecialization appear to have lagged behind the rest of the world [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation